Measurements of nitric oxide and total reactive nitrogen in the Antarctic stratosphere - Observations and chemical implications - Fahey, D. W.; Kelly, K. K.; Murphy, D. M.; Proffitt, M. H.; Eubank, C. S.; Ko, M. K. W.; Ferry, G. V.; Loewenstein, M.; Chan, K. R. (1989)
Results are presented on measurements of NO and the sum of reactive nitrogen species, NO(y), which include NO, NO2, NO3, N2O5, HNO3, and ClONO2 (in addition to ClO, O3, H2O, and N2O measurements), obtained aboard the NASA ER-2 aircraft flying over the Antarctica between the latitudes of 53 and 72 deg S during the Airborne Antarctic Ozone Experiment. The boundary of the chemically perturbed region (CPR), as indicated by a sharp increase in the level of ClO, occurred near 66 deg S; outside or equatorward of the CPR, the NO(y) mixing ratios ranged between 6 and 12 ppbv, with values decreasing poleward and reaching total NO(y) levels of 4 ppbv or less within 5-deg poleward of the boundary. Data presented in this paper clearly associate the Antarctic ozone decrease with perturbed conditions of ClO, NO(y), and H2O, which are in turn associated with processes defined as nonstandard heterogeneous chemistry, denitrification, and dehydration, respectively.